Extracellular matrix protein 1 gene mutation in turkish patients with lipoid proteinosis - Dertlioglu, Selma Bakar; Edgunlu, Tuba Gokdogan; Sen, Deniz Erol; Suzek, Tugba Onal (Wolters Kluwer Medknow Publications, 2019)
Background: Lipoid proteinosis (LP) is a rare autosomal recessive genodermatosis characterized by mucocutaneous lesions and hoarseness of voice that develop in early childhood. LP is caused by mutation in the extracellular matrix protein 1 (ECM1) gene, which is located on 1q21.2. Aims: This study aimed to present the profile of ECM1 gene mutations and to identify possible novel mutations specific to Turkey. Materials and Methods: The ECM1 gene mutations of 19 LP patients from five families were evaluated using DNA isolated from peripheral blood samples. All ten exons in the ECM1 gene region were amplified by polymerase chain reaction (PCR). The PCR products were analyzed using a DNA sequencing analyzer. The results of DNA sequencing were analyzed with bioinformatics methods. Results: of the 19 LP patients evaluated in our study, we detected defects in exon 6 (c.507delT, 658T>G), exon 9 (157C>T, 727C>T), and exon 10 (c.93_94delGCinsTT) of the ECM1 gene. Conclusions: Our results indicate that defects in exons 6, 9, and 10 of the ECM1 gene were responsible for LP in our country. The identification of these pathogenic mutations is valuable because it facilitates early diagnosis and genetic counseling.
Keywords: Extracellular matrix protein 1; genetic; lipoid proteinosis; mutation